Growth hormone deficiency and hypobetalipoproteinemia in a patient with Kabuki syndrome: a case report - Madeo, Simona Filomena; Di Caprio, Antonella; Tagliafico, Enrico; Iughetti, Lorenzo (Acta Biomedica Atenei Parmensis, 2024)
Kabuki syndrome (KS) is a rare condition characterizeb by facial features (eversion of the lower lateral eyelid, arched eyebrows with the lateral one-third dispersed or sparsed, depressed nasal tip, and prominent ears), skeletal anomalies, dermatoglyphic abnormalities, short stature, and mental retardation. We describe a case of KS clinically diagnosed at 7 years of life on the basis of typical facial features, neurodevelopment delay, and growth failure; the diagnosi was gentically confirmed later in adolescence. Endocrinogy investigation performed for short stature revealed growth hormone deficiency (GHD). The treatment with rhGH from 8 years of life initially improved height velocity and stature, however the catch-up growth was only transient and final height was disappointing. The patient, investigated also for the presence of altered lipid profile, showed hypobetalipoproteinemia (HBL). At the best of our knowledge, this is the first case of KS with both GHD and HBL in literature. This case reinforces the awareness for the necessity to take in account that  syndromes can combine with different unexpected genetic conditions in many cases.